KINERJA APARATUR SIPIL NEGARA STUDI KASUS KANTOR KECAMATAN MOROTAI SELATAN KABUPATEN PULAU MOROTAI - Ibnu Kanaha (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
The purpose of this study was to determine the performance of employees (ASN) in the South Morotai District office. The form of this research is descriptive qualitative, with data collection techniques through observation and in-depth interviews with the subdistrict head, subdistrict head secretary, employees, and the community. This study concluded that employees at the South Morotai District Office were not disciplined in terms of time, both when they entered the office and after working hours. Employees are not able to make the best use of time to do productive work to improve performance. employees generally do not know and understand their respective fields of duty. The concept of the right man in the right place is not applied in the placement of employees. Performance evaluation of employees at the South Morotai District Office is difficult because of unclear job descriptions and division of tasks for the state apparatus. This causes the work performance is not measurable both in quality and quantity..